Video Formats Used by Extension to Distribute Videotapes to Field Staff - Carla Rich (Journal of Applied Communications, 1986)
The Cooperative Extension Service has a long history in the use of electronic delivery systems. From its earliest beginnings, Extension has adopted information tools to extend its outreach.